(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
On the beach of Puerto Arista, Chiapas, street vending is a common sight. Every day, vendors walk long distances-sometimes several kilometers-to offer their products or services during peak tourist hours. The objective of this research was to analyze the perspective of beach vendors regarding the products they sell and how these are designed to capture the attention of tourists in order to increase sales. A mixed-methods approach was applied, combining both quantitative and qualitative elements within a descriptive research design. A survey was conducted with 50 individuals representative of this group, aiming to identify their demographic characteristics, the products they sell, and how their work is related to family, social, and economic aspects.